The Ayyubid Orogen: An Ophiolite Obduction-Driven Orogen in the Late Cretaceous of the Neo-Tethyan South Margin - Şengör, A.M.; Stock, Joann (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2014)
A minimum 5000-km long obductiondriven orogeny of medial to late Cretaceous age is located between Cyrenaica in eastern Libya and Oman. It is herein called the Ayyubid Orogen after the Ayyubid Empire that covered much of its territory. The Ayyubid orogen is distinct from other Alpide orogens and has two main parts: a western, mainly germanotype belt and an eastern mainly alpinotype belt. The germanotype belt formed largely as a result of an aborted obduction, whereas the alpinotype part formed as a result of successful and large-scale obduction events that choked a nascent subduction zone. The mainly germanotype part coincides with Erich Krenkel’s Syrian Arc (Syrischer Bogen) and the alpinotype part with Ricou’s Peri-Arabian Ophiolitic Crescent (Croissant Ophiolitique péri-Arabe). These belts formed as a consequence of the interaction of one of the now-vanished Tethyan plates and Afro-Arabia. The Africa-Eurasia relative motion has influenced the orogen's evolution, but was not the main causative agent. Similar large and complex obduction-driven orogens similar to the Ayyubids may exist along the Ordovician Newfoundland/ Scotland margin of the Caledonides and along the Ordovician European margin of the Uralides.